Dupilumab relieves pruritus both in uremic pruritus and in atopic dermatitis with chronic kidney disease: a retrospective real-world study - Wang, Qian; Yang, Ge; Zhou, Xiyuan; Zhong, Xiang; Liu, Jie; Zhang, Lixia (Frontiers in Medicine, 2025)
BackgroundTreatment methods for pruritus in patients with chronic kidney disease (CKD) are lacking. Exploring the therapeutic potential of dupilumab in alleviating pruritus in CKD patients has good clinical value.ObjectivesThis retrospective study aims to analyze the effectiveness and safety of dupilumab in atopic dermatitis (AD) patients with CKD and uremic pruritus (UP) patients.MethodsDemographic and clinical data from AD patients with CKD stages 3–5 and UP patients who received dupilumab treatment were retrospectively analyzed. Improvements in pruritus were assessed via Peak Pruritus Numerical Rating Scale (PP-NRS) and 5-D itch scale (5-D IS) at weeks 2, 4, 12, and 16. Eczema Area and Severity Index (EASI) and Atopic Dermatitis Control Tool (ADCT) scores were also recorded at week 16 in AD patients with CKD. Safety during treatment was observed.ResultsAfter dupilumab treatment, the PP-NRS and 5D-IS scores of 12 AD patients with CKD and 10 UP patients were significantly decreased. The percentages of UP patients who achieved PP-NRS ≥ 4-point improvement and 5D-IS ≤ 10-point at week 4, 12, and 16 did not significantly differ from those of AD patients with CKD (p > 0.05). At week 16, the skin symptoms in AD patients significantly improved (66.67% achieved EASI-75). No significant adverse effects were found.ConclusionDupilumab safely and effectively reduced pruritus in UP patients in the short term and achieved a comparable anti-pruritus effect to AD patients with CKD.